Pemanfaatan Financial technology dalam upaya peningkatan ekonomi daerah tertinggal dan pemberdayaan UMKM di daerah Brebes, Jawa Tengah - Fina Rohmatul Ummah; Darmawan Darmawan (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
This research aims to determine the benefits of the presence of financial technology in empowering Micro, Small, and Medium Enterprises (MSMEs) to enhance the economy in Brebes Regency, Central Java. The study adopts a descriptive quantitative and qualitative methodology, gathering data from various sources, various internationally accredited journals, and the Central Statistics Agency. The findings of this research indicate that financial technology has proven to be an effective tool in assisting MSMEs to enhance the economy. By leveraging financial technology appropriately, MSMEs can improve access to capital, operational efficiency, market reach, and financial literacy. Ultimately, this can stimulate the growth of MSMEs and enhance the well-being of the community in Brebes Regency, Central Java.